Biometric data sharing in the wild: Investigating the effects on online sports spectators. Issue 105 (September 2017) - Curmi, Franco; Ferrario, Maria Angela; Whittle, Jon
Abstract: There has been a market surge in both provision of and demand for fitness applications and sport wearables. These wearables often come equipped with highly sophisticated biometric data (e.g. heart rate) functionalities that make the capture and sharing of such biometric data increasingly common practice. A few research studies have considered the effect that sharing biometric data has on those individuals sharing this data. However, little is known regarding the social impact of sharing this data in real-time and online. In this study, we investigate whether there is value in sharing heart rate data within social applications and whether sharing this data influences the behavior of those seeing this data. We do so by conducting a study where the heart rate data of runners competing in a 5-km road race is shared in real-time with 140 online spectators. We collect rich quantitative data of user interaction though server logs, and a qualitative data set through interviews and online users' comments. We then compare and contrast the behavior of online spectators who are presented with heart rate data together with contextual data, and those who are only presented with contextual data, for example, location. We also examine whether this difference is dependent on the social relation between the athletes and the spectators. Results indicate that spectators who are presented with the runners' heart rate data support the athletes more and rate the presented system more positively. These effects are dependent on the social tie between the athletes and spectators. This is one of the first studies to carry out an empirical investigation in the wild on the effects of sharing heart rate data in an online social context. In this light, in addition to supporting earlier literature, the outcomes present new insights and research directions within the sporting context. Abstract : Highlights: It reports on the online behavioral differences between spectators who are presented only with context data and spectators who are presented with both biometric and context data. It reports on the online behavioral differences between friendsourced and crowdsourced spectators. We then compare disparities between the four groups in conditions 1 and 2 above. Results indicate that the most engaged spectators are friendsourced spectators who view additional heart rate data. Finally, we draw upon these results with support from the collected qualitative data that was collected in this study and its relation to existing literature.